2006
DOI: 10.1099/jmm.0.46500-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of virulence genes in Campylobacter jejuni isolates in Bahrain

Abstract: There are no data describing the genetic make-up of Campylobacter strains (an important aetiological agent of diarrhoea) circulating in the Arabian Gulf region. Here, the molecular characterization of two virulence genes in Campylobacter jejuni from Bahrain and the relationship with clinical infection are reported. Molecular screening for cytolethal distending toxin (cdtB) and invasion-associated marker (iam) genes was carried out on C. jejuni stool isolates collected from January 2002 to January 2004 in Bahra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
(24 reference statements)
5
24
1
2
Order By: Relevance
“…strains from children. Similar results were obtained by Al-Mahmeed et al (2006). However, Rizal et al (2010) estimated iam gene occurrence in human C. jejuni samples to be 77.7%.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…strains from children. Similar results were obtained by Al-Mahmeed et al (2006). However, Rizal et al (2010) estimated iam gene occurrence in human C. jejuni samples to be 77.7%.…”
Section: Discussionsupporting
confidence: 77%
“…It has been linked with subsequent development of Guillain-Barré syndrome (GBS), which usually develops 2 up to 3 weeks after the initial illness (van Doorn 2009). This wide range of clinical symptoms cannot be explained as pertaining only to the host's response; characteristics of the bacterial pathogen may contribute (Rożynek et al 2005, Al-Mahmeed et al 2006. Adherence, invasion and cytotoxin production appear to be essential virulence factors (Wardak et al 2006).…”
mentioning
confidence: 99%
“…In accordance with our findings, other studies regarding the prevalence of VAGs worldwide also found a very high proportion of these genes in different types of clinical and animal samples (Datta et al, 2003;Al-Mahmeed et al, 2006;Talukder et al, 2008;Ripabelli et al, 2010;Andrzejewska et al, 2011;Hamidian et al, 2011), especially ciaB (95-98 %) and the cdtABC operon (85-100 %).…”
Section: Information From Elisa Testssupporting
confidence: 80%
“…This differed from a previous report that found a higher rate of detection of two VAGs in one particular symptomatic group (Al-Mahmeed et al, 2006). Once again, this lack of association may be caused by geographical factors or individual circumstances relating to the Campylobacter infections.…”
Section: Information From Elisa Testscontrasting
confidence: 56%
“…Utvrđeno je, da je nivo antitela na Campylobacter jejuni mnogo viši kod dece koja žive u zemljama u razvoju, a utvrđeni su i blaži klinički oblici bolesti u odnosu na decu iz razvijenih zemalja (12). O patogenezi kampilobakterioze i razvoju posledičnog protektivnog imuniteta u toku infekcije, danas se vrlo malo zna (13).…”
unclassified